A new termite (Isoptera: Termitidae: Termitinae: Proboscitermes) from Tanzania - Scheffrahn, Rudolf H.; O’malley, Robert C. (Zootaxa, 2010)
A new species of termite, Proboscitermes mcgrewi Scheffrahn, is described from soldiers, workers, and a physogastric queen collected along the northeastern shore of Lake Tanganyika. The new species differs from all other mandibulate termite soldiers in having a relatively large proportion of head capsule volume anterior to the mandibular articulations.